Anisotropy of eddy variability in the global ocean. (November 2015) - Stewart, K.D.; Spence, P.; Waterman, S.; Sommer, J. Le; Molines, J.-M.; Lilly, J.M.; England, M.H.
Highlights: Anisotropy of ocean variability is rich in horizontal and vertical structure. Variability near bathymetry is highly anisotropic and oriented with isobath. Barotropic (baroclinic) variability is (in)sensitive to bathymetric slope. Results offer guidance for parameterizing barotropic variability in ocean models. Abstract: The anisotropy of eddy variability in the global ocean is examined in geostrophic surface velocities derived from satellite observations and in the horizontal velocities of a 1/12° global ocean model. Eddy anisotropy is of oceanographic interest as it is through anisotropic velocity fluctuations that the eddy and mean-flow fields interact dynamically. This study is timely because improved observational estimates of eddy anisotropy will soon be available with Surface Water and Ocean Topography (SWOT) altimetry data. We find there to be good agreement between the characteristics and distributions of eddy anisotropy from the present satellite observations and model ocean surface. In the model, eddy anisotropy is found to have significant vertical structure and is largest close to the ocean bottom, where the anisotropy aligns with the underlying isobaths. The highly anisotropic bottom signal is almost entirely contained in the barotropic variability. Upper-ocean variability is predominantly baroclinic and the alignment is less sensitive to the underlying bathymetry. These findings offer guidance for introducing a parameterization of eddy feedbacks, based on the eddy kinetic energy and underlying bathymetry, to operate on the barotropic flow and better account for the effects of barotropic Reynolds stresses unresolved in coarse-resolution ocean models.